Impacts of intensive dairy production on smallholder farm women in coastal Kenya - Mullins, G.; Wahome, L.; Tsangari, P.; Maarse, L. (Springer, 1996)
Welfare impacts of an intensive dairy technology package on women and their families are investigated on 32 smallholder crop-livestock farms in the sub-humid zone of Kilifi District, Coast Province, Kenya. Farms were stratified according to male or female extension contact. A female enumerator interviewed the wife or female head of household on each farm regarding her present and past household responsibilities and the effects of the intensive dairy enterprise on these duties and upon the welfare of the household. On three-quarters of the male contact farms, dairy operators were women. Across all farms, women performed half of all dairy-related activities, but only on female contact farms did income from the dairy enterprise accrue to women in proportion to their labor input. The equitable return of benefits to labor corresponded with better dairy unit performance on female contact farms, where women also indicated greater access to and autonomy over household resources and decision-making. Irrespective of extension contact, there was broad consensus among the women interviewed that intensive dairying has led to improved household welfare, primarily through increased household income and milk consumption. There was also wide agreement, however, that these gains have been achieved at the expense of more work for women. Women on female contact farms were observed spending dairy income on food for the household and childrens' schooling more often than their counterparts on male contact farms. Based on these and other findings, the study concludes that gender of the extension contact, dairy operator and farm owner were determinants of the intra-household impacts of intensive dairying on the smallholder farms in this study. Recommendations for design and delivery of livestock technologies for crop-based farming systems, with special emphasis on how to minimize negative impact on vulnerable household members, are inferred from study findings.